Active head rotation in benign positional paroxysmal vertigo - Ganança,Fernando Freitas (2009)
Benign Positional Paroxysmal Vertigo (BPPV) is one of the most common vestibular diseases and the active head rotation test one of the most modern methods of vestibular function assessment. AIM: this study aims to verify if the active head rotation test may reveal signs of horizontal and/or vertical vestibulo-ocular reflex dysfunction in vertigo patients suspected for BPPV. STUDY DESIGN: retrospective series study. MATERIALS AND METHOD: Neurotological evaluation including computerized electronystagmography and active head rotation on the horizontal and vertical axes were conducted in 100 patients suspected for BPPV patients. Results: Isolated or associated abnormalities of the horizontal and/or vertical vestibulo-ocular reflex gain, phase and symmetry were indicative of vestibular involvement and found in 77.0% of the BPPV patients. CONCLUSION: the active head rotation test revealed horizontal and/or vertical vestibulo-ocular reflex dysfunctions in a relevant number of BPPV patients.